Prevalence of Physical Activity Requirements Among US Colleges/Universities Participating in the American College Health Association-National College Health Assessment II. (April 2022) - Bailey, Caitlin P.; Lowry, Mark; Napolitano, Melissa; Hoban, Mary T.; Kukich, Christine; Perna, Frank M.
Physical activity requirements (PAR; ie, courses required for graduation) have been proposed as a policy solution for increasing undergraduate physical activity. This study aimed to report prevalence of PAR among US colleges/universities participating in the American College Health Association-National College Health Assessment (ACHA-NCHA) and to understand whether these requirements were associated with campus characteristics. Data from the American College Health Association-National College Health Assessment II serial cross-sectional survey (2015–2019) were merged with researcher coded variables (2019): binary PAR status, nature of PAR (activity-based, conceptual, or combination), and number of courses required to fulfill the PAR. Logistic regression determined whether campus characteristics were associated with PAR in 2019. Nonparametric tests examined differences in nature and number of PAR courses. Of 379 schools, 59 (15.6%) had PAR, with 36 (61.0%) having activity-based PAR and 23 (39.0%) having a combination. Compared to public and four-year schools, private (OR=3.47 [1.77, 6.80]) and two-year schools (OR=6.55 [2.21, 19.45]) had significantly increased odds of having PAR. Private schools required significantly more PAR courses compared to public schools (2.42 vs. 1.73, P=.005). PAR were less prevalent in this sample than reported historically, indicating need for campus leadership attention to this issue. Research is needed to understand what barriers exist to implementing and maintaining PAR on college/university campuses, particularly among public and four-year schools. Understanding health promotion practices among ACHA member schools, which have made leadership commitments to promote student health, can provide greater knowledge of PAR barriers and best practices in schools across the United States and globally.